Strategi Manajemen Konflik Pendidikan AUD di Masa Pandemi - Rusdiana Navlia; Danang Prastyo; Azhar Amrullah Hafizh; Sofia Mubarokah Sa’bana (Universitas Al-Hikmah Indonesia, 2021)
In educating the nation's life, the Indonesian government's policy in the education sector that supports lifelong education is the recognition of early childhood education. Conflict is something that cannot be avoided in life. In social interaction and internalization between individuals or between groups. Conflict is actually a natural thing, even as long as human life is always faced and struggles with conflict. In the past, conflict was seen as a symptom or phenomenon that was unnatural and had negative or positive consequences depending on how to manage it. Currently, many parents may still misunderstand the definition and purpose of early childhood education. This is understandable considering the function of early childhood education in several cities or regions, early childhood education which is actually an educational institution to develop the character and personality of children is more often understood as a place of day care.